PENGARUH GAYA KEPEMIMPINAN KEPALA SEKOLAH TERHADAP KINERJA GURU DI SMP NEGERI LOTAS AMANATUN UTARA - Reto, Romana; Dau, Yoseph Lodowik Deki; Bria, Florens Maxi Un (Sekolah Tinggi Pastoral St. Petrus Keuskupan Atambua, 2023)
The purpose of this study was to find out the description and influence of the principal's leadership style on teacher performance at SMPN Negeri Lotas Amanatun Utara. This research uses quantitative methods. The sample in this study was 25 people consisting of 1 school principal, 22 teachers, and 2 employees. The data collection technique in this study was using a questionnaire, while the data analysis technique used descriptive statistical data analysis and inferential statistical data analysis. The results showed that the variable description of the principal's leadership style and teacher performance at SMP Negeri Lotas Amanatun Utara was in the good category, where the achievement of the variable indicator of the principal's leadership style was 66.4%, and the achievement indicator of the teacher's performance variable was 70.2%. In the influence test, the results obtained explained that there was a positive and significant influence of the principal's leadership style on teacher performance at Lotas Amanatun Utara Public Middle School. This is shown through the results of the inferential test where the principal's leadership style variable has a t value of 3,471. This t value is a significant value because the sig value is 0.002 or less than the specified 0.05 (alpha).